Keuntungan Aglomerasi Kawasan Ekonomi Khusus (KEK) Sei Mangkei Terhadap Peningkatan Efisiensi Industri Wilayah Sekitarnya - Umar Maya Putra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2015)
Special Economic Zones (SEZs) Sei Mangkei located in Simalungun has a location adjacent to the Port Hub International Kuala Tanjung. Location of KEK Sei strategic Mangkei connected by train along the 20 miles of High City to Kuala Tanjung. Railroad construction is planned to be completed and can be used in 2014. Intermodal connectivity between KEK Sei Mangkei to the Port of Kuala Tanjung very necessary to reduce stagnation and damage to roads and to support the customs facilities required in a special economic zone. In the establishment of special economic zones, will create an interconnected agglomeration that can improve the industry for the surrounding area and the spirit of entrepreneurship. In the study contained in www.kemenperin.go.id/artikel/22/ explained that a number of industries are being and will be built in the area of Palm Oil Industrial Cluster Sei Mangke, North Sumatra, which was built to increase the added value of palm oil in Indonesia. Besides the addition of plant oil kelaps (MCC) PTPN 3 with a total capacity of 75 tons per hour, also will be built a few other industries. Start of power plant 2 x 35 mega watt, will also be built palm kernel oil mill berkapsitas 400 liters per day, biodiesel plants.